Pendampingan Literasi Digital di SDN 2 Pomahan Kecamatan Pulung Kabupaten Ponorogo - Rifky Kamila Ramadhani; Nanik Setyowati; Lisma Meilia Wijayanti (Social Science Academic, 2025)
The purpose of this community service research is to introduce and increase digital literacy knowledge for early childhood. The method used is a qualitative method with an ABCD (Asset Based Communiy Development) approach that emphasizes empowerment, understanding of the potential and challenges possessed to improve quality individually and in groups. The object of this service is students in grades 4-6 of SDN 2 Pomahan. The result of this community service is an increase in insight or information in the world of digital literacy for children. This service is carried out in order to prepare children so that they are not easily carried away in the form of negative impacts with the development of increasingly sophisticated technology and so that they can adapt properly through the use of digital media, especially gadgets effectively and ethically. The conclusion of this service is a positive contribution in terms of gadget utilization and how to process the information obtained properly.